Algorithms at War: The Promise, Peril, and Limits of Artificial Intelligence. Issue 3 (24th June 2019) - Jensen, Benjamin M; Whyte, Christopher; Cuomo, Scott
Abstract: How might rapid advances in artificial intelligence (AI) technologies affect the construction and application of military power? Despite the emerging importance of AI systems in defense modernization initiatives, there has been little empirical or theoretical study from the perspective of the international relations (IR) and security studies fields. This article addresses this shortcoming by describing AI developments and assessing the manner in which AI is likely to affect military organizations. We focus specifically on military power, as new methods and modes thereof will alter the constitution of security relationships around the world and affect the ability of states to bargain, signal, and influence in the twenty-first century. We argue that, though rapid adoption of AI technologies stands to transform states' ways of war on a number of fronts, an AI revolution brings with it new forms of risk that must be reconciled with the widespread integration of algorithmic systems across military functions. Where new technology promises a transformation of the character of military power in some veins, it also complicates the cognitive aspects of decision-making and bureaucratic interactions in security institutions. The speed with which complex integrated AI systems enable entirely new modes of war also stands to detach human agency in a potentially destabilizing fashion from the conduct of warfare on several fronts. Preventing the negative externalities of these "ghosts in the machine" will involve significant efforts to educate decision makers, promote accountability, and restrain irresponsible employment of AI.